ISSUES OF RAISING SINGING SKILLS IN PRESCHOOL CHILDREN - G.Shodiyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides instructions on the training of singing skills in preschool children, rules for singing spoons, exercises for the development of breathing, breathing.